ChatGPT as a Feedback Provider: Arab Students' Perceptions of AI-Based Writing Evaluation in Academic English - Abdullah Alshayban (Ijaz Arabi Journal of Arabic Learning, 2026)
The research has four constructs, including perceived usefulness, trust and accuracy, motivation, and behavior intention, which indicate the perceptions of EFL students regarding ChatGPT as a feedback tool in English writing. The mixed-methods design was used to collect data (N = 254) on surveys and open-ended responses. Quantitative methods (descriptive statistics, reliability, regression, and mediation) indicated that ChatGPT was the most useful tool overall for enhancing readers' grammar, organization, and clarity. Its performance was impressive, but its accuracy was inconsistent, with occasional gaps in context. The regression showed that perceived usefulness, trust, and motivation were all useful predictors of behavioral intention, and that motivation mediated the effect of usability on behavioral intention. This was supported by the qualitative results, which focused on ChatGPT's immediacy and supportiveness. ChatGPT is a useful, supplementary source of feedback compared to a teacher's because it helps foster a student's self-confidence and self-reliance when editing drafts.